Spectroscopic Investigations of Co(II) and Cu(II) Interaction with Imatinib Mesylate and Capecitabine - Cipurković, Amira; Horozić, Emir; Crnkić, Aida; Marić, Snježana; Ljubijankić, Nevzeta (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2016)
Cobalt and copper are present as trace elements in biological systems andthey are very important for the activity of many enzymes with different functions inthe body. Their biological functions derive from the possibility of potential interactionof their M(II) ions with O, N and S donor atoms of various ligands and biomoleculesin the living organisam. Capecitabine and imatinib mesylate (ImM) are synthetic organiccompounds which are used in a treatment of some oncological diseases thus disturbinghomeostasis of biological system.In this study, UV and FTIR spectroscopic methods are used to investigate metalligand interactions and products of their interaction at physiological conditions using model test systems. FTIR spectrum of Co(II)-capecitabine model systems show lack of absorption bands characteristic for -OH (at 3230 cm-1) and C=O groups positioned at pyrimidine cycle (at 1718 cm-1) for pure capecitabine. It indicates interaction of Co(II) ion with capecitabine via O-donor atoms. FTIR spectrum of pure ImM deviates from spectrum of Co(II)-ImM system at 1250-1050 cm-1 wavelength region. This region corresponds to peaks characteristic for mesylate ions (O3S-CH3), which indicates on interaction between Co(II) and donor atoms containing molecule ligands (O and/or S). UV results for model systems of M(II) with capecitabine and ImM show similar absorption bands as those of pure ligand, while absobances are different (except for Cu(II)-ImM). Since these investigations are done at approximately at physiological conditions, it is expected that, after application of these ligands as pharmacological agents, the same interactions are happening in the human body. .